Development and validation of the new Investigator® Argus X-12 QS Kit. (December 2015) - Scherer, M.; König, M.; Bussmann, M.; Prochnow, A.; Peist, R.
Abstract: We developed and validated the Investigator Argus X-12 QS Kit, which allows co-amplification of 12 X-chromosomal markers arranged in 4 linkage groups. The updated kit uses the Fast Reaction Mix 2.0 that allows short PCR cycling protocols and provides high inhibitor tolerance. The autosomal marker D21S11 was added to enable alignment of the Investigator Argus X-12 QS Kit profile with a profile from any other autosomal STR kit from the expanded CODIS or ESS markers, and to minimize the risk of sample mix-ups. A Quality Sensor (QS) was introduced as an internal control to monitor PCR performance. SNP primers were added to overcome allele drop out due to known mutations in primer binding sites. Furthermore, more alleles were added to the allelic ladder.